Silicon attenuates aluminum toxicity in sugarcane plants by modifying growth, roots morphoanatomy, photosynthetic pigments, and gas exchange parameters - da Silveira Sousa Junior, Gilmar [UNESP]; Hurtado, Alexander Calero [UNESP]; de Cassia Alves, Rita [UNESP]; Gasparino, Eduardo Custodio [UNESP]; dos Santos, Durvalina Maria Mathias [UNESP] (Springer Nature, 2024)
Aluminum (Al) inhibits growth and limits plant productivity in acidic soils. An important strategy to increase Al tolerance is the use of silicon (Si) nutrition. Thus, the aim of this study was to evaluate the interactive role of Si in increasing the growth, physiological and morphoanatomy responses of sugarcane plants under Al toxicity. A 4 × 2 factorial scheme in a completely randomized design was used to study the impact of Si (2 mM) on attenuating Al toxicity (0, 10, 15 and 20 mg L−1, as Al2(SO4)3·18H2O) in sugarcane seedlings. After 45 days, Al toxicity affected sugarcane growth by increasing Al uptake and accumulation, modifying root growth, thickness, and morphoanatomy, and decreasing pigment content, gas exchange parameters, and the number of adaxial and abaxial stomata. However, Si attenuated Al toxicity in the sugarcane seedlings by limiting Al uptake and transport to the shoots, causing positive changes in root morphoanatomy, higher pigment content, improving gas exchange parameters, thereby increased growth. Furthermore, cultivar ‘CTC9003’ showed beneficial impacts from Si supplementation than ‘CTC9002’, especially under Al toxicity. The findings of this study suggest that Si plays a notable role in improving anatomical and physiological aspects, particularly the growth of sugarcane seedlings under Al toxicity.